2017
DOI: 10.1002/adem.201700608
|View full text |Cite
|
Sign up to set email alerts
|

A Hierarchically Porous Carbon Fabric for Highly Sensitive Electrochemical Sensors

Abstract: The hierarchically porous carbon fabrics with controlled conductivity and hydrophilicity have been fabricated by dual templating method of soft templates nested on hard templates. A non‐woven fabric coated with a solution of F127/resol has been carbonized for the synthesis of both macro‐porous structures of 10–15 µm in diameter having meso‐porous carbon structures of 4–6 nm, respectively. After carbonization treatment, not only conductivity is significantly improved, the hierarchically porous carbon also shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The contact angle of the MCF is 47.56° while that of the OMCF is only 13.45°. This markedly enhanced wettability is probably due to the ordered hierarchically porous structure of the OMCF, which facilitates the ions to enter the material interior quickly and therefore improve the CDI performance. , …”
Section: Resultsmentioning
confidence: 99%
“…The contact angle of the MCF is 47.56° while that of the OMCF is only 13.45°. This markedly enhanced wettability is probably due to the ordered hierarchically porous structure of the OMCF, which facilitates the ions to enter the material interior quickly and therefore improve the CDI performance. , …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the PC 900 -modified GCE, which exhibited the smallest semicircle and lowest R ct value compared to other electrodes showed excellent catalytic performance due to the rapid electron transfer process on the carbon surface layers (see Figure S5a, Supporting Information). Several works ,, have been reported that higher surface areas and larger pore structures are favorable for electrocatalytic applications because the mass transport of the electrolyte is facilitated to obtain higher catalytic currents. In this work, the PC 900 -modified GCE possesses larger pore structures that enable the electrolyte solution to flow into/out of PC more easily, thus resulting in better electrocatalytic performance.…”
Section: Resultsmentioning
confidence: 99%
“…Afterward, organic/inorganic moieties are adopted as the precursors to synthesize carbon materials, but the treatment is costly and unfriendly to the environment . Recently, sustainable PC derived from biomass or earth-abundant renewable resources has attracted much attention because it is relatively effective, environmentally friendly, and simple in the synthesis approach. For instance, Liu et al studied the nitrogen-doped carbon derived from biomass (grass), and the carbon-rich nanomaterial was exhibited as a promising fluorescent sensing platform for the label-free detection of Cu­(II) ions . Huang et al developed the amorphous oxygen-doped carbon nanosheet (O@CN) from tannin which was applied as the electrocatalyst for efficient N 2 fixation to NH 3 under ambient conditions .…”
Section: Introductionmentioning
confidence: 99%
“…1D PCNs have unique linear porous nanostructures such as carbon nanofibers,, carbon nanotubes, carbon nanorods and possess short radial diffusion paths of ions. To date, a large amount of work has been dedicated to the controllable synthesis of 1D PCNs with tailored morphology, porosity and surface properties through different synthesis approaches.…”
Section: Multiscale Pcns and Their Preparation Methodsmentioning
confidence: 99%